Dynamometer Resistance Pad Position Influences Knee Strength and Hamstring/Quadriceps Ratio in Professional Basketball Players: Retrospective Observational Study - Raúl Coto Martín; María Jesús Martínez Beltrán; Néstor Pérez Mallada; Lucía Cuéllar Marín; Oscar Otín Arroyo; Pablo José Borrás Luján; Juan Manuel Arribas-Marín (Applied Sciences)
Some knee strength measuring devices have an anterior cushioning area but relies on a belt for the posterior pad adjustment, creating an uneven force distribution. This study analyzed whether the distal pad position affects knee strength measurements. Eleven professional basketball players participated in this study, with a total of 22 knees evaluated. Knee flexion and extension dynamometric measurements were performed at different angular velocities: 30°/s, 120°/s, and 240°/s. For each angular velocity, two measurements were performed with varying positions of the measuring tool pad at the anterior and posterior aspects (AA and PA). The hamstring/quadriceps (H/Q) ratio was calculated by dividing the hamstring musculature’s maximum peak strength by the quadricep musculature’s maximum peak strength at each measurement. The knee work was extracted from the device after finishing the measurements. Significant differences were found between measurement positions in the knee flexion force at 30°/s (p < 0.001) and 120°/s (p = 0.027). No differences were found for the extension forces. As for the H/Q ratio, significant differences were found between positions at 30°/s (p < 0.001). Furthermore, significant differences between positions were found for the knee work at 120°/s (p = 0.019). These findings suggest that the positioning of the pad on the leg directly influences knee flexor strength measurements, which in turn impacts critical parameters, such as the H/Q ratio and knee work. Given the importance of these variables in injury prevention, particularly for conditions such as anterior cruciate ligament (ACL) injuries, ensuring precise and reliable measurement methods is essential. We recommend using the PA position because it increases knee flexion strength values, potentially leading to more accurate assessments of the muscle function and balance.